2016
DOI: 10.1039/c5py01858g
|View full text |Cite
|
Sign up to set email alerts
|

Lights on! A significant photoenhancement effect on ATRP by ambient laboratory light

Abstract: The influence of ambient laboratory light from common fluorescent lamps on AGET, ARGET, and classical ATRP reactions was investigated and significant differences were found except for ARGET ATRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…50% to activator regeneration while at higher concentration of AIBN, 0.2 equiv with respect to ATRP initiator, the contribution dropped to ca. 15%.The effects of ambient light on normal and ARGET ATRP were also investigated [94]. An enhancement in polymerization rate was observed with ambient light under normal ATRP conditions, but not under ARGET ATRP conditions.…”
mentioning
confidence: 99%
“…50% to activator regeneration while at higher concentration of AIBN, 0.2 equiv with respect to ATRP initiator, the contribution dropped to ca. 15%.The effects of ambient light on normal and ARGET ATRP were also investigated [94]. An enhancement in polymerization rate was observed with ambient light under normal ATRP conditions, but not under ARGET ATRP conditions.…”
mentioning
confidence: 99%
“…[58][59][60] Subsequently, it was discovered that photopolymerization also occurs in the absence of added photoinitiator. [61,62] The photochemical process was originally proposed to occur through an activation of the Cu I activator complex, [63,64] and a dissociation of the Cu II -halogen bond in the excited state, [30,61,65] although subsequent studies showed the need for external electron donors (amines). [54] This leads to a revised mechanism with an excited state reaction between Cu II and amines, leading to oxidation of the amine to a N-centered radical cation, and a reduction of the Cu II complex to a Cu I species.…”
Section: Mechanistic Considerations In Photoinduced Atrp (Photoatrp)mentioning
confidence: 99%
“…Choi et al [12] used ATRP to conjugate osteogenic growth factor, bone morphogenetic protein 2 (BMP-2), to a titanium surface with polyethylene glycol (PEG)-methacrylate. Although researchers are hesitant to use ATRP for biomedical applications due to slow reaction times and residual impurities from use of metal catalysts [11,13], Rainier et al [14][15][16] introduced photo accelerated ATRP which has been joined by metal-free ATRP reactions [13,16]. The attachment of proteins containing integrin-binding RGD sequences facilitate improved biocompatibility through stronger cell attachment to implant surfaces.…”
Section: Introductionmentioning
confidence: 99%